Minority carrier blocking to enhance the thermoelectric performance of solution-processed BixSb2 – xTe3 nanocomposites via a liquid-phase sintering process - Zhang, Chaohua (2020)
Minority carrier blocking through heterointerface barriers has been theoretically proposed to enhance the thermoelectric figure of merit (ZT) of bismuth telluride based nanocomposites at elevated temperatures recently (Phys. Rev. B2016, 93, 165209). Here, to experimentally realize the minority carrier blocking, a liquid-phase sintering process enabled by excess Te is applied to the solution-processed BixSb2–xTe3 nanocomposites to introduce interfacial energy barriers. The controlling parameters in the liquid-phase sintering process such as the amount of excess Te, sintering temperature and holding time, and the Bi composition (x) are systemically tuned and investigated to fully understand the minority carrier blocking mechanism. These interface-engineering parameters are optimized for introducing maximum lattice imperfections and band-bending interfaces that are responsible for blocking the minority carrier and wide-range scattering of the phonons toward enhanced thermoelectric performance. High ZT > 1.4 at 375 K is realized in the Bi0.5Sb1.5Te3 sample, which is much higher than those of the state-of-the-art commercial ingots (ZT ∼ 1) and other solution-processed nanocomposites. The enhanced ZT at elevated temperatures is mostly due to the suppression of bipolar thermal conductivity by minority carrier blocking as well as the reduction of lattice thermal conductivity. Adapting this solution synthesis process to design favorable heterointerfaces for minority carrier blocking in the liquid-phase sintering process holds promise to further enhance the ZT values.